2017
DOI: 10.1016/j.chiabu.2017.02.026
|View full text |Cite
|
Sign up to set email alerts
|

Young men’s suicidal behavior, depression, crime, and substance use risks linked to childhood teasing

Abstract: The consequences in adulthood of bullying, teasing, and other peer victimization experiences in childhood rarely have been considered in prospective studies. Studies of peer victimization are mixed regarding whether negative outcomes are explained by pre-existing child vulnerabilities. Furthermore, replication of prior studies with broader definitions and other methods and demographic groups is needed. Based on mother, father, and teacher reports at ages 10–12 years, we classified American boys (n = 206) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 48 publications
0
16
0
5
Order By: Relevance
“…Although most research on peer victimization focuses on bullying involving repeated aggression by more powerful peers, bullying is not the only detrimental peer victimization experience children can have (see Finkelhor, Turner, & Hamby, 2012). Indeed, peer teasing in childhood also is associated with concurrent problems and long-term negative outcomes in adulthood (e.g., Kerr, Gini, & Capaldi., 2017). Thus, further research is needed to document both the risk for and long-term consequences of peer victimization involvement in childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Although most research on peer victimization focuses on bullying involving repeated aggression by more powerful peers, bullying is not the only detrimental peer victimization experience children can have (see Finkelhor, Turner, & Hamby, 2012). Indeed, peer teasing in childhood also is associated with concurrent problems and long-term negative outcomes in adulthood (e.g., Kerr, Gini, & Capaldi., 2017). Thus, further research is needed to document both the risk for and long-term consequences of peer victimization involvement in childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, rates of retention were remarkably high, minimizing this potential bias as a concern. Finally, prior work with this sample indicates that teasing experiences at age 12 years predicted a diverse array of negative psychosocial outcomes, including suicide attempt, clinically significant depressive symptoms, arrest, and patterned tobacco use, [14] some of which persisted following adjustment for the potent childhood risks considered presently. Thus, it is possible that obesity is not among the myriad long-term negative consequences of childhood bullying and teasing.…”
Section: Discussionmentioning
confidence: 99%
“…Our prior work indicates that the measures of being teased used in the current study are predictive of serious long-term adjustment problems, particularly among victims who also tease other children. [14] Third, the sample size was relatively small; power was greater than 80% to detect a group difference on BMI of approximately a one-half standard deviation using a t-test. Fourth, research is needed in samples that include women, as a recent meta-analysis found that obesity was more strongly associated with a childhood history of maltreatment in studies that included more women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations